2018
DOI: 10.3390/antib7020016
|View full text |Cite
|
Sign up to set email alerts
|

Small-Format Drug Conjugates: A Viable Alternative to ADCs for Solid Tumours?

Abstract: Antibody–Drug Conjugates (ADCs) have been through multiple cycles of technological innovation since the concept was first practically demonstrated ~40 years ago. Current technology is focusing on large, whole immunoglobulin formats (of which there are approaching 100 in clinical development), many with site-specifically conjugated payloads numbering 2 or 4. Despite the success of trastuzumab-emtansine in breast cancer, ADCs have generally failed to have an impact in solid tumours, leading many to explore alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 94 publications
0
61
0
1
Order By: Relevance
“…However, poor penetration into solid tumors still poses a problem for ADCs as well as naked therapeutic antibodies. On the other hand, small‐molecular drug conjugates are expected to overcome this issue . The binding activity and specificity for FR of FolateSiR‐1 are thought to be high as well as anti‐FRs antibodies, and so FolateSiR‐1 might be available as a basic scaffold for the development of new small‐molecular drug conjugates to treat FR‐expressing ovarian cancer.…”
Section: Resultsmentioning
confidence: 99%
“…However, poor penetration into solid tumors still poses a problem for ADCs as well as naked therapeutic antibodies. On the other hand, small‐molecular drug conjugates are expected to overcome this issue . The binding activity and specificity for FR of FolateSiR‐1 are thought to be high as well as anti‐FRs antibodies, and so FolateSiR‐1 might be available as a basic scaffold for the development of new small‐molecular drug conjugates to treat FR‐expressing ovarian cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Although the immunoglobulin G (IgG) portion of the ADC is important for maintaining a long halflife, binding to target, and internalizing drug into tumor cells, its large size presents a physical barrier to efficient extravasation across blood vessel walls and diffusion through tumors (29). This has prompted a significant effort to explore alternative formats to traditional IgGs, including antibody fragments, alternative scaffolds, natural ligands, and small molecules (30). Three drug conjugates using smaller targeting domains have now entered the clinic.…”
Section: Overview Of Adcs In Clinical Developmentmentioning
confidence: 99%
“…[3,4,5] However,t echnological challenges still need to be overcome to improvet he therapeutic index (TI, defined as the maximum tolerated dose divided by the minimum efficaciousd ose) of ADCs,p articularly those used to treat solid tumors and those prepared using PBDs. [17] Severale fforts have recently been made to improvet he TI of ADCs, including 1) site-specificc onjugation, which offers precise drug loading and optimal serum stability, [1] 2) fractionated doses of PBD ADCs, which maintain antitumor activity and have greater tolerability than single high doses, [18] and 3) improvements in tumor penetration of small-fragmentADCs. [19] Recently we reported that lowering the number of drugs per antibodya nd using ar ebridging conjugation strategy with ad ual maleimide PBD (SG3710) could be as trategy to improve the TI of an anti-HER2 antibody.…”
Section: Discussionmentioning
confidence: 99%
“…[16,17] Small fragments derived from IgGs or from other highly structured scaffolds derived from natural proteins have found use as ADCs. [10,11,18] Antibody fragments may be ideal formats as ADC cancer therapeuticsb ecause they could have higher tumoru ptake, ab etter tumor-to-blood ratio, and faster clearance than full-length antibodies. [10,11,18] The former may be a desirable propertyi nc ases where toxicities to healthy tissues can increase with prolonged exposures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation